The association between reflective function and global functionality in patients with borderline personality disorder. (December 2021) - Bezerra, Glaydcianne Pinheiro; Laskoski, Pricilla Braga; Terra, Luciana; Ramos-Lima, Luis Francisco; Serralta, Fernanda Barcellos; Hauck, Simone
Objective: To examine the association between reflective function and global functionality in borderline personality disorder (BPD) patients, controlling for symptomatology and defensive style. Method: Thirty-nine female inpatients were evaluated employing a sociodemographic questionnaire, the Structured Clinical Interview for Personality Disorders-II (SCID-II), the Self-Reporting Questionnaire (SRQ-20), the Reflective Functioning Questionnaire (RFQ), the Defence Style Questionnaire-40 (DSQ-40) and the Global Assessment of Functioning (GAF). Results: Functionality was inversely associated with the reflective function uncertainty score (–.458; p < .01) and neurotic defences (–.335; p < .05). Symptom severity (SRQ-20) was associated with the use of immature defences (–.445; p < .01). The association between functionality and the reflective function uncertainty score remained significant, even when controlled for symptoms and defensive style ( p = .002). Conclusion: The ability to mentalise seems to play a central and somehow independent role in BPD psychopathology.